2022
DOI: 10.1186/s13007-022-00892-0
|View full text |Cite
|
Sign up to set email alerts
|

High throughput analysis of leaf chlorophyll content in sorghum using RGB, hyperspectral, and fluorescence imaging and sensor fusion

Abstract: Background Leaf chlorophyll content plays an important role in indicating plant stresses and nutrient status. Traditional approaches for the quantification of chlorophyll content mainly include acetone ethanol extraction, spectrophotometry and high-performance liquid chromatography. Such destructive methods based on laboratory procedures are time consuming, expensive, and not suitable for high-throughput analysis. High throughput imaging techniques are now widely used for non-destructive analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 48 publications
(42 reference statements)
5
35
0
1
Order By: Relevance
“…In this study, HSI data outperformed machine vision image data in SVM-based models for distinguishing AMM, AM and SM seeds, which aligns well with studies comparing these approaches for classifying kernels of rice ( Fabiyi et al., 2020 ) and maize ( Tu et al., 2022 ), as well as comparing chlorophyll content in sorghum leaves ( Zhang et al., 2022a ). It is likely that machine vision data resulted in lower accuracy in classifying AMM and AM seeds because the features extracted by machine vision were purely morphological phenotypes.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, HSI data outperformed machine vision image data in SVM-based models for distinguishing AMM, AM and SM seeds, which aligns well with studies comparing these approaches for classifying kernels of rice ( Fabiyi et al., 2020 ) and maize ( Tu et al., 2022 ), as well as comparing chlorophyll content in sorghum leaves ( Zhang et al., 2022a ). It is likely that machine vision data resulted in lower accuracy in classifying AMM and AM seeds because the features extracted by machine vision were purely morphological phenotypes.…”
Section: Discussionsupporting
confidence: 86%
“…Hyperspectral imaging (HSI) has been a powerful tool for the comprehensive analysis of agricultural and food production that integrates spectroscopy and machine vision to collect both spectral and spatial information from one target [ 15 , 16 , 17 , 18 ]. HSI represents the spectra at each pixel of an image, utilizing the advantages of near-infrared spectroscopy, conventional imaging, and even multispectral imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for measuring chlorophyll content include a method based on absorption of light by a water-soluble acetone extract of chlorophyll, and a method based on the absorbance or reflectance of light of a specific wavelength by an intact leaf using a portable chlorophyll meter [ 43 ]. However, these destructive methods based on laboratory procedures such as acetone-ethanol extraction, spectrophotometry, and high-performance liquid chromatography are time-consuming, expensive, and not suitable for high-throughput analysis [ 44 ]. Chlorophyll mainly determines the color of plant leaves, which indicates the nutritional and health status of plants, and it has been demonstrated that plant nutrient levels, water availability, plant diseases, and aging have a significant effect on plant leaf color [ 45 ].…”
Section: Discussionmentioning
confidence: 99%